Development of mobile book tracing system / Nur Farihah Amdi Suapri - Amdi Suapri, Nur Farihah (2017)
Mobile Book Tracing System is a mobile system that helps staff and students at UiTM Shah Alam trace the information of books by only clicking at their hand. These projects aims are to build a book tracing system that help librarians trace the ownership of the returned books or when they want to manage their book rack. The application can help librarians trace the information of the books with their own phones without check it manually by looking to the color tag placed beside the cover books. The system helps in ease librarians work since it is portable, easy to use and can install in any android phones. So, librarian can scan the books and get the information from where the books are from, either from Perpustakaan Tun Abdul Razak (PTAR) 1, PTAR 2 or PTAR 3. It also will reduce technical error since using color tag caused problems to them because it can be easily remove and broken. It also can reduce human error since librarians might do mistakes in matching tag color and placed of the books. The objective of this project are to identify the requirement for book tracing system using barcode, to design a book tracing system and to develop a web based book tracing system and meet user expectation. For this project, the Mobile Application Development Life Cycle is used in developing this mobile application because it is suit with the development plan strategies. Interview is conducted as a project findings in order to get the requirements that librarians need. In short, Book Tracing System would be able to give a perfect and useful information to librarians in order for them manage the book.